3D numerical simulation of a directly irradiated bubbling fluidized bed with SiC particles. (25th May 2021) - Díaz-Heras, M.; Córcoles, J.I.; Belmonte, J.F.; Almendros-Ibáñez, J.A.
Abstract: This paper presents the numerical results obtained in a directly irradiated fluidized bed. The numerical model was implemented using CPFD-Barracuda software coupled with a P-1 radiation model. The bed consists of a cylindrical geometry containing SiC particles, with a diameter of 7.62 cm and a fixed bed height of 8 cm. The irradiation on the top of the bed was implemented by including a high temperature surface that directly irradiated on the top of the bed, with a uniform radiation flux of 3 × 1 0 4 kW ∕ m 2 . The work studies the influence of the airflow rate and the thermal behavior of the irradiated bed. The results show that increases in the airflow rate (up to 2.5 times the minimum fluidization conditions) notably enhance the mixing rate and the agitation levels on the top of the bed, reducing the appearance of hot spots on the top surface, with the bed exhibiting a more uniform temperature in its upper half. At higher airflow rates, the maximum temperature of the directly irradiated particles is reduced from 454 K to 384 K when the airflow rate is increased from 1.5 to 2.5 times the minimum fluidization airflow rate. In contrast, the mean temperature of the whole bed of particles rises (from 315.9 K to 327.5 K), increasing the storage efficiency. Highlights: Numerical simulation of a directly irradiated fluidized bed is carried out. A hot disk on the top allows to simulate the irradiation level on the particles. A time step of 10 −3 s was selected due to their balance between precision and time. Hot spots are observed on the top at low air velocities ( U = 1 . 5 U m f ). High airflow rates promotes mixing in the bed and reduce maximum temperature.